The Impact of Macroeconomic variables on the credit provided by Saudi Banks - Abdel Rahim, Eyas Jafar (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to examine the impact of macroeconomic variables of the Saudi economy as in Gross Domestic Product (GDP), Government Expenditure (G), Economic Openness (OPE), Inflation Rate (CPI) and the Bank Deposits (DS) on the credit provided by Saudi banks (BF), on annual time series data between 1970-2012. To investigate this relationship, the study used Autoregressive Distributed Lag method (ARDL) to measure the long-run and short-run impact, At that the E-views 8.1 has been used for analyze the cointegration,the diagnostic, the reliability - stability tests, and the forecasting behavior of the model. The study found that (BF) is affected positively by (GDP) growth rate in the long-run. Also the (BF) has been affected negatively in the short and long-run by inflation rates (CPI) and government expenditure (G). Consequently the Contractionary Fiscal Policy in recent period will not lead to reduce the financial performance of Saudi banks, and the growth of (GDP) in the future will have positive impact on the financing capacity of the Saudi banking sector.